Factors associated with elevated low-density lipoprotein cholesterol levels among hill tribe people aged 30 years and over in Thailand: a cross-sectional study - Niwed Kullawong; Tawatchai Apidechkul; Panupong Upala; Ratipark Tamornpark; Vivat Keawdounglek; Chanyanut Wongfu; Fartima Yeemard; Siriyaporn Khunthason; Chalitar Chomchoei (BMC, 2021)
Abstract Background Low-density lipoprotein cholesterol (LDL-C) is one of the most important types of cholesterol and has an impact on health. Certain lifestyle and dietary habits in different populations may leads to increased levels of LDL-C, particularly among those with poor education and economic statuses, such as hill tribe people in Thailand. This study aimed to estimate the prevalence of and determine the factors associated with high LDL-C levels among hill tribe people in northern Thailand. Methods A cross-sectional study was performed to gather information from six main hill tribe populations: Akha, Lahu, Hmong, Yao, Karen, and Lisu. Individuals who were aged over 30 years and living in 30 selected hill tribe villages were invited to participate in the study. A validated questionnaire and 5-mL blood specimens were used to obtain data. Correlation analyses, chi-square tests, t-tests, and logistic regression were used to detect correlations and associations. Results A total of 2552 participants were recruited into the study; 65.9% were females, and 64.1% were aged younger than 60 years old. Approximately 69.6% of participants had abnormal LDL-C levels; 33.6% had above-optimal levels, 24.3% had borderline high levels, 8.0% had high levels, and 3.7% had very high levels. A total of 17.4% of participants had low high-density lipoprotein cholesterol (HDL-C) and high LDL-C levels, while 14.9% had high triglyceride and LDL-C levels. After controlling for sex, age, religion, education, annual family income, and marital status in the multivariate model, three variables were found to be associated with high LDL-C levels: occupation, the amount of lard used in daily cooking, and glycated hemoglobin (HbA1c). Those who were working as agriculturalists had a 1.34-fold greater chance of having abnormal LDL-C than traders and others (95% CI = 1.09-1.34). Those who used moderate and high quantities of lard in their daily cooking had a 1.45-fold (95% CI = 1.15-1.82) and 1.31-fold (95% CI = 1.04-1.68) greater likelihood of having abnormal LDL-C levels than those who used low quantities, respectively. Those who had abnormal HbA1c levels were less likely to develop abnormal LDL-C levels than those who had normal HbA1c levels (AOR = 0.69, 95% CI = 0.51-92). Conclusions Effective public health programs that do not conflict with the cultures of hill tribes are urgently needed, particularly programs encouraging the use of small quantities of lard for daily cooking practices.